PENGEMBANGAN ENSIKLOPEDIA KEANEKARAGAMAN HEWAN VERTEBRATA BERBASIS SPESIMEN - Anandita Eka Setiadi; Ety Setiawati (Bioscientist : Jurnal Ilmiah Biologi, 2016)
ABSTRACT: The collection of Unmuh Pontianak Integrated Laboratory specimens represents the diversity of vertebrate animals from West Kalimantan. As a learning resource, the specimen can be used as an object of observation that provides a direct learning experience and as a source of written information that can be packaged in encyclopedia book form. The purpose of this study is to produce a valid encyclopedia of vertebrate animals based on a valid specimen and receive a positive response from learners. Output target of this research is product and publication. Research method used is Research and Development (R & D). The development model used is 4-D modification (four D model) with 3 stages namely: (1) Define (Define). (2) Design (Design), and (3) Development (Develop). While at stage (4) Disseminate will not be done due to limited time and cost. The results showed that the developed encyclopedia was considered valid in both good and excellent category. The results of validator assessment include aspects of material presentation of 98% (very good), aspect image 100% (very good), 96% language aspect (very good), and aspect 84% (good) graphic component. Student response to encyclopedia developed on encyclopedia presentation aspect, ease of use of encyclopedia, and activity of learners learn of encyclopedia each get 82% response (very strong). While on the aspect of ease of learners understand the encyclopedia 80% (strong) and interest in encyclopedia 75% (strong). Overall it can be concluded that the developed encyclopedia is valid and get positive response from learners.